Psychological stressors and life satisfaction among university students during the Second Wave of covid-19: Moderating role of resilience - Tania Qamar; Saralah Devi Mariamdaran Chethiyar; Muhammad Ali Equatora (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2021)
Purpose - The purpose of the research was to examine the relationship between psychological distress and life satisfaction among university students during the second wave of COVID-19, also to assess the moderating role of resilience. Method - The population of this study is university students. The selection of samples in the current research using purposive sampling strategy and selected 200 students. The data were analyzed using correlation analysis, hierarchical regression analysis, and path analysis.Result - The results show the psychological distress has a significant negative relationship with life satisfaction and resilience has a significant positive relationship with life satisfaction. Regression findings reveal that psychological distress and resilience were significant predictors of life satisfaction. Moderation findings show the resilience plays a significant moderating role between psychological distress and life satisfaction.Implications – The current research suggests improving the skills performance in the life of students. The present study helps to understand the importance of life satisfaction, especially among university students.Originality – This is the first study that used intervening variables psychological distress, resilience, and life satisfaction. It is not only particular for professionals or students to be aware of psychological distress toward life satisfaction in the Pakistani society but also to be educated about the culture itself and clinical area.***Tujuan - Penelitian ini bertujuan untuk mengkaji hubungan antara tekanan psikologis dengan kepuasan hidup mahasiswa selama gelombang kedua COVID-19, serta menilai peran moderasi resiliensi.Metode - Populasi dalam penelitian ini adalah mahasiswa. Pemilihan sampel dalam penelitian ini menggunakan strategi purposive sampling dan dipilih 200 siswa. Analisis data menggunakan analisis korelasi, analisis regresi berjenjang, dan analisis jalur.Hasil - Hasil penelitian menunjukkan tekanan psikologis memiliki hubungan negatif yang signifikan dengan kepuasan hidup dan resiliensi memiliki hubungan positif yang signifikan dengan kepuasan hidup. Temuan regresi mengungkapkan bahwa tekanan psikologis dan ketahanan merupakan prediktor signifikan dari kepuasan hidup. Temuan moderasi menunjukkan ketahanan memainkan peran moderasi yang signifikan antara tekanan psikologis dan kepuasan hidup.Implikasi - Penelitian saat ini menyarankan peningkatan kinerja keterampilan dalam kehidupan siswa. Studi ini membantu untuk memahami pentingnya kepuasan hidup, terutama di kalangan mahasiswa.Originalitas - Ini merupakan penelitian pertama yang menggunakan variabel intervening tekanan psikologis, resiliensi, dan kepuasan hidup. Tidak hanya bagi para profesional atau pelajar untuk menyadari tekanan psikologis terhadap kepuasan hidup dalam masyarakat Pakistan tetapi juga untuk dididik tentang budaya itu sendiri dan area klinis.